The vascular nature of lung‐resident mesenchymal stem cells. (24th August 2020) - Steens, Jennifer; Klar, Lea; Hansel, Christine; Slama, Alexis; Hager, Thomas; Jendrossek, Verena; Aigner, Clemens; Klein, Diana
Abstract: Human lungs bear their own reservoir of endogenous mesenchymal stem cells (MSCs). Although described as located perivascular, the cellular identity of primary lung MSCs remains elusive. Here we investigated the vascular nature of lung‐resident MSCs (LR‐MSCs) using healthy human lung tissue. LR‐MSCs predominately reside within the vascular stem cell niche, the so‐called vasculogenic zone of adult lung arteries. Primary LR‐MSCs isolated from normal human lung tissue showed typical MSC characteristics in vitro and were phenotypically and functionally indistinguishable from MSCs derived from the vascular wall of adult human blood vessels (VW‐MSCs). Moreover, LR‐MSCs expressed the VW‐MSC‐specific HOX code a characteristic to discriminate VW‐MSCs from phenotypical similar cells. Thus, LR‐MSC should be considered as VW‐MSCs. Immunofluorescent analyses of non‐small lung cancer (NSCLC) specimen further confirmed the vascular adventitia as stem cell niche for LR‐MSCs, and revealed their mobilization and activation in NSCLC progression. These findings have implications for understanding the role of MSC in normal lung physiology and pulmonary diseases, as well as for the rational design of additional therapeutic approaches. Abstract : Although the precise stem cell niche(s) of lung‐resident mesenchymal stem cells (LR‐MSCs) remain(s) elusive, lung injury following a pathological trigger might at least be partially mediated by endogenous MSCs. Here we show that LR‐MSCs predominately reside within the vascular stem cell niche, the so‐called vasculogenic zone of adult lung arteries, and reveal their mobilization and activation in lung cancer progression.